The effect of surface observation angle on accuracy of non-contact temperature measurement method - Oborsky, Gennady; Levinskiy, Aleksandr; Holofieieva, Maryna (Technology audit and production reserves, 2017)
Thermal control by IR devices is a fairly difficult task, because it depends on a large number of external factors. The greatest error of contactless temperature measurement method is unknown or variable emissivity of the surface of the object. This is due to the fact that the ability of the object to emit infrared radiation can vary because it is depended on the material, properties of the surface, observation direction, and in the case of some materials – on temperature. Technological audit was conducted to identify the variation characteristics of emissivity coefficient in terms of thermal control. The aim of audit was to determine the effect of observation angle on the emissivity coefficient. Using thermal imager and auxiliary equipment it was found that with the measurement error is increased with increase of observation angle and may reach 50 %. The authors conducted a series of experiments confirming the effect of observation angle on accuracy of temperature measurement, and proposed dependencies allowing to reduce the value of absolute error of measurement using IR devices to several degrees that in relative form less than 1 %. Research results will improve the accuracy of temperature measurement by taking into account an effect of observation angle on emissivity coefficient of the object, normalize image thermograms for different sections of the object, as well as the select possible defective areas on the thermogram to determine the uniformity of thermal field.